Automated control system and processing of object temperature parameters - Nigmatov Azizjon; Sherbaev Murod; Mukhamedkhanov Ulugbek; Yeshmatova Barno; Yunusova Sayyora (E3S Web of Conferences, 2024)
This article is devoted to the research and development of intelligent object temperature control systems. We will consider the relevance of using such systems in modern industry, pose problems related to temperature control, propose solutions that include machine learning methods and optimization algorithms, and draw conclusions about the applicability of this approach.